Algozes ou vítimas: uma análise das reportagens sobre o adolescente em conflito com a lei, publicadas em 2015 nos portais eletrônicos de notícias Gazeta do Povo e Paraná Online, a partir da teoria do etiquetamento - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
This work has as object of study the content present in the journalistic discourse of reports, whose theme is on the issue of adolescence / crime, which were broadcast in 2015 in the electronic news portals Gazeta do Povo and Paraná Online. The choice of these two portals occurred because they deal more portals accessed by Paraná in 2015. It was used to collect these portals occurred from pre-determined key terms (adolescents in conflict with the law, juvenile delinquents and juvenile offenders) which appear as available in the aforementioned homepages. It is aimed in this research: to analyze the historical elements that permeate the issue of adolescents in conflict with the law in Brazil; reflect on the scene of the crime involving teenagers nowadays and the media approach to this issue; identify the content of media discourses conveyed in electronic portals circulating on the Internet more accessible by Paraná in 2015; analyze the existence of stigmatizing elements or stereotypes builders in the media discourse. The empirical data obtained in this study were treated and systematized from the content analysis method, which ensured objectivity and clarity, allowing through the election and categories of analysis arising of the articles could be chosen the theoretical basis of this research, which is anchored in the concepts from the Labeling Theory. Before this, there were general analysis of the reports and their relation to the chosen portals later, the twenty articles selected were interpreted from four categories: Conflict in Adolescent concept with the law, Causes of Genesis Conflict with law, presented solutions in the Reports for adolescent Issues in Conflict with s law and Care for adolescents in Conflict with the law. the research resulted in a broadening of the perception of the media related to the theme of adolescent / crime, a greater understanding the process of manipulation of adolescent deteriorated identity to which is assigned to practice offense, leading to understand how is the process of building the stereotype of this teenager from the media approach.
Algozes ou vítimas: uma análise das reportagens sobre o adolescente em conflito com a lei, publicadas em 2015 nos portais eletrônicos de notícias Gazeta do Povo e Paraná Online, a partir da teoria do etiquetamento
Keywords: adolescente; Etiquetamento; estigma e estereótipo; adolescent; Labeling; stigma and stereotype; CNPQ::CIENCIAS SOCIAIS APLICADAS